Analisis Peran BAPPEDA Pada Perencanaan Pendapatan Asli Daerah (PAD) Di Labuhan Batu - Muhammad Reza Mahendra; Hendra Harmain (Jurnal Riset Akuntansi, 2023)
The research was conducted to find out the role of BAPPEDA in planning Regional Original Income (PAD) in Medan City. This research uses descriptive qualitative methods with data collection techniques, namely interviews and documentation. The results of this research explain that the source of Medan City's Original Regional Income comes from land and building taxes. Apart from that, there are supporting and inhibiting factors in planning the Regional Original Income of Medan City. The role of the Development Planning Agency in planning the Regional Original Income of the City of Medan is to provide recommendations for reports that must be accurate and up-to-date as well as good work programs in order to create the vision and mission that the City of Medan hopes for.